Outer packaging material for power storage device, method for producing same, and power storage device
By using a hot-welding resin layer of polypropylene and polyethylene in the outer packaging material for power storage devices and controlling the island area ratio of its island structure, the molding problem caused by poor compatibility between polypropylene and polyethylene is solved, and the molding problem is achieved. The effect of suppressing whitening and reducing insulation is achieved.
Patent Information
- Application Number
- CN202411391376.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-17
- Filing Date
- 2020-07-17
- Publication Date
- 2024-12-24
AI Technical Summary
Among the existing outer packaging materials for power storage devices, polypropylene and polyethylene are not compatible, which leads to fine cracks during molding of the hot-welded resin layer, which reduces insulation and causes whitening problems.
The outer packaging material consisting of a laminated body of a base material layer, a barrier layer and a hot-weld resin layer. The hot-weld resin layer includes polypropylene and polyethylene, and the island structure is observed through a scanning electron microscope and the island area is The proportion is controlled to 80.0% or more to suppress whitening and insulation reduction caused by molding.
The whitening of the hot-welded resin layer and the reduction of insulation properties are effectively suppressed, and the performance of the outer packaging material for power storage devices is improved.
Smart Images

Figure CN119181905A_ABST
Abstract
Description
[0001] This case is filed on July 17, 2020 、Application No. 202080051621.6(PCT / JP2020 / 027784) 、The name of the invention is Outer packaging material for power storage device, method for producing the same, and power storage device A divisional application for a patent application. Technical Field
[0002] The present invention relates to an outer packaging material for an electricity storage device, a method for producing the outer packaging material, and an electricity storage device. Background Art
[0003] At present, various types of power storage devices have been developed, but no matter what type of power storage device, an outer packaging material for encapsulating power storage device components such as electrodes and electrolytes is an indispensable component. At present, as an outer packaging material for power storage devices, metal outer packaging materials are mostly used.
[0004] On the other hand, in recent years, with the high performance of electric vehicles, hybrid electric vehicles, personal computers, cameras, mobile phones, etc., the power storage devices are required to have various shapes, and to be thinner and lighter. However, the metal outer packaging materials for power storage devices currently used are difficult to cope with the diversification of shapes and have a limit to lightness.
[0005] To this end, in recent years, as an outer packaging material for a storage battery device that can be easily processed into a variety of shapes and is thinner and lighter, a film-like laminate having a base layer / barrier layer / thermo-fusible resin layer laminated in sequence has been proposed (for example, refer to Patent Document 1).
[0006] In such an outer packaging material for a storage device, a recess is usually formed by cold forming, and storage device elements such as electrodes and electrolyte are arranged in the space formed by the recess. Then, a heat-fusible resin layer is heat-fused to obtain a storage device in which the storage device elements are accommodated inside the outer packaging material for the storage device.
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent Application Publication No. 2008-287971
[0010] Patent Document 2: Japanese Patent Application Publication No. 2013-101778 Summary of the invention
[0011] Problems to be solved by the invention
[0012] In the film-like packaging material for a power storage device, polyolefins such as polypropylene are sometimes used as a material for forming the heat-fusible resin layer. For example, when polypropylene is used to form the heat-fusible resin layer, polyethylene is sometimes used simultaneously to improve processability and flexibility.
[0013] However, the compatibility of polypropylene and polyethylene is not high. For example, when a small amount of polyethylene is added to polypropylene and a heat-fusible resin layer is formed by melt extrusion molding, a sea island structure in which islands of polyethylene are dispersed is formed in the sea of polypropylene (it should be noted that in order to observe the sea island structure, the cross section of the heat-fusible resin layer is stained with ruthenium tetroxide or the like, and the cross-sectional image is obtained using a scanning electron microscope for observation). Therefore, when the outer packaging material for the storage device is subjected to the above-mentioned cold molding, due to the stress applied during molding, fine cracks are generated at the interface between the polypropylene part and the polyethylene part of the heat-fusible resin layer, which sometimes leads to whitening of the heat-fusible resin layer and reduction of the insulation of the outer packaging material for the storage device.
[0014] For example, Patent Document 2 states that when the inner layer of a battery outer packaging material is formed of a mixture of a polypropylene resin and a polyethylene resin, the size and number of the "islands" can be controlled by controlling the manufacturing conditions of the battery outer packaging material, the thickness of the inner layer, the mixing ratio of the polypropylene resin and the polyethylene resin, etc., thereby controlling the sealing strength between the heat-sealed inner layers. It is also stated that the particle size of the polyethylene resin as the size of the "islands" in the sea-island structure mixture is preferably in the range of 0.5 to 5 μm (i.e., 0.196 to 19.6 μm). 2 about).
[0015] However, the inventors of the present invention have studied and found that, as disclosed in Patent Document 2, the particle size of the polyethylene resin in the conventional battery packaging material containing polypropylene and polyethylene in the inner layer is large and whitening and reduction in insulation properties due to molding cannot be sufficiently suppressed.
[0016] Under such circumstances, a main object of the present invention is to provide an outer packaging material for a power storage device having a thermally fusible resin layer containing polypropylene and polyethylene and suppressing whitening and reduction in insulation properties due to molding.
[0017] Methods for solving problems
[0018] The inventor of the present invention conducted in-depth research to solve the above-mentioned problems. As a result, it was found that the outer packaging material for a storage device as described below can suppress the whitening and reduction of insulation caused by molding. The outer packaging material for a storage device is composed of a laminate having at least a base material layer, a barrier layer and a heat-fusible resin layer in order from the outside to the inside, and the heat-fusible resin layer contains polypropylene and polyethylene. For the cross-section of the heat-fusible resin layer in the direction parallel to the TD (Transverse Direction) and the thickness direction, an island structure can be observed in the cross-sectional image obtained using a scanning electron microscope. In the cross-sectional image, relative to the total number of islands in the island structure, the area of the island is 0.02μm 2 The total number of the following island portions accounts for more than 80.0%. The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion of 12.5% thickness, assuming that the total thickness of the layers located on the inner side of the barrier layer is 100%. It should be noted that the MD direction and TD direction of the heat-fusible resin layer laminated on the laminate can generally be determined based on the barrier layer described later. That is, in the outer packaging material for the storage battery device, the MD and TD of the barrier layer described later can generally be determined during its manufacturing method. For example, when the barrier layer is composed of aluminum foil, linear stripes called rolling marks are formed on the surface of the aluminum foil in the rolling direction (RD: Rolling Direction) of the aluminum foil. Since the rolling marks extend along the rolling direction, the rolling direction of the aluminum foil can be grasped by observing the surface of the aluminum foil. In addition, in the manufacturing process of the laminate, generally, the MD of the laminate is consistent with the RD of the aluminum foil. Therefore, by observing the surface of the aluminum foil of the laminate, the rolling direction (RD) of the aluminum foil can be determined, and thus the MD of the laminate (that is, the MD of the heat-fusible resin layer) can be determined. In addition, the TD of the laminate is a direction perpendicular to the MD of the laminate, so the TD of the laminate (that is, the TD of the heat-fusible resin layer) can also be determined.
[0019] The present invention has been completed through further research based on these findings. That is, the present invention provides the invention of the embodiments described below.
[0020] The present invention provides an outer packaging material for a power storage device, which is composed of a laminate having at least a base material layer, a barrier layer and a heat-fusible resin layer in order from the outside to the inside.
[0021] The heat-fusible resin layer comprises polypropylene and polyethylene.
[0022] A sea-island structure can be observed in a cross-sectional image of the heat-adhesive resin layer taken in a direction parallel to TD and in the thickness direction using a scanning electron microscope.
[0023] The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%.
[0024] In the cross-sectional image, the area of the islands is 0.02 μm with respect to the total number of islands in the sea-island structure. 2 The ratio of the total number of the following island portions is 80.0% or more.
[0025] Effects of the Invention
[0026] According to the present invention, there can be provided a packaging material for a power storage device having a heat-fusible resin layer containing polypropylene and polyethylene and suppressing whitening and reduction in insulation due to molding. In addition, according to the present invention, there can be provided a method for manufacturing the packaging material for a power storage device and a power storage device. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 It is a schematic diagram showing an example of the cross-sectional structure of the outer packaging material for a power storage device of the present invention.
[0028] Figure 2 It is a schematic diagram showing an example of the cross-sectional structure of the outer packaging material for a power storage device of the present invention.
[0029] Figure 3 It is a schematic diagram showing an example of the cross-sectional structure of the outer packaging material for a power storage device of the present invention.
[0030] Figure 4 It is a schematic diagram showing an example of the cross-sectional structure of the outer packaging material for a power storage device of the present invention. DETAILED DESCRIPTION
[0031] The outer packaging material for a storage device of the present invention is characterized in that it is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in order from the outside to the inside, the heat-fusible resin layer contains polypropylene and polyethylene, and a cross-sectional image of the heat-fusible resin layer in a direction parallel to TD and in a thickness direction is obtained using a scanning electron microscope to observe an island structure, the cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer side to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%, and in the cross-sectional image, the area of the island portion is 0.02 μm with respect to the total number of island portions of the sea-island structure. 2The total number of the following island portions accounts for 80.0% or more. According to the packaging material for a power storage device of the present invention, by having such a configuration, whitening and a decrease in insulation due to molding can be suppressed.
[0032] Hereinafter, the outer packaging material for a power storage device of the present invention will be described in detail. It should be noted that in this specification, the numerical range indicated by "to" means "above" or "below". For example, the expression 2 to 15 mm means above 2 mm and below 15 mm.
[0033] 1. Laminated structure of outer packaging material for power storage device
[0034] The outer packaging material 10 for a power storage device of the present invention is, for example, Figure 1 As shown, it is composed of a laminated body in which a base material layer 1, a barrier layer 3 and a heat-fusible resin layer 4 are laminated in this order. In the outer packaging material 10 for a storage device, the base material layer 1 is the outermost layer, and the heat-fusible resin layer 4 is the innermost layer. When assembling a storage device using the outer packaging material 10 for a storage device and a storage device element, the storage device element is accommodated in a space formed by heat-fusible peripheral portions of the outer packaging material 10, with the heat-fusible resin layers 4 of the storage device outer packaging material 10 facing each other.
[0035] For example, the outer packaging material 10 for a power storage device is Figure 2 to Figure 4 As shown in FIG. 1 , an adhesive layer 2 may be provided between the base layer 1 and the barrier layer 3 for the purpose of improving the adhesion between these layers. Figure 3 and Figure 4 As shown in FIG. 1 , an adhesive layer 5 may be provided between the barrier layer 3 and the heat-fusible resin layer 4 for the purpose of improving the adhesion between these layers. Figure 4 As shown, a surface coating layer 6 or the like may be provided on the outer side (the side opposite to the heat-fusible resin layer 4 side) of the base material layer 1 as required.
[0036] The thickness of the laminate constituting the outer packaging material 10 for a storage device is not particularly limited, but preferably is about 180 μm or less, about 155 μm or less, or about 120 μm or less from the viewpoint of reducing costs and improving energy density, etc. In addition, the thickness of the laminate constituting the outer packaging material 10 for a storage device is preferably about 35 μm or more, about 45 μm or more, or about 60 μm or more from the viewpoint of maintaining the function of the outer packaging material for a storage device such as protecting the storage device element. In addition, the preferred range of the thickness of the laminate constituting the outer packaging material 10 for a storage device can be, for example, about 35 to 180 μm, about 35 to 155 μm, about 35 to 120 μm, about 45 to 180 μm, about 45 to 155 μm, about 45 to 120 μm, about 60 to 180 μm, about 60 to 155 μm, about 60 to 120 μm, and about 60 to 155 μm is particularly preferred.
[0037] In the outer packaging material 10 for a storage device, the ratio of the total thickness of the base material layer 1, the adhesive layer 2 provided as required, the barrier layer 3, the adhesive layer 5 provided as required, the heat-fusible resin layer 4, and the surface coating layer 6 provided as required is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more, relative to the thickness (total thickness) of the laminate constituting the outer packaging material 10 for a storage device. As a specific example, when the outer packaging material 10 for a storage device of the present invention includes the base material layer 1, the adhesive layer 2, the barrier layer 3, the adhesive layer 5, and the heat-fusible resin layer 4, the ratio of the total thickness of these layers is preferably 90% or more, more preferably 95% or more, and even more preferably 98% or more, relative to the thickness (total thickness) of the laminate constituting the outer packaging material 10 for a storage device.
[0038] 2. Forming each layer of the outer packaging material for the power storage device
[0039] [Base material layer 1]
[0040] In the present invention, the base material layer 1 is a layer provided for the purpose of fulfilling the function as a base material of the outer packaging material for a power storage device, etc. The base material layer 1 is located on the outer layer side of the outer packaging material for a power storage device.
[0041] There is no particular limitation on the material forming the base layer 1 as long as it has a function as a base material, that is, at least has insulating properties. The base layer 1 can be formed using, for example, a resin, and the resin may contain additives described below.
[0042] When the substrate layer 1 is formed by a resin, the substrate layer 1 may be, for example, a resin film formed by a resin, or a substrate formed by coating a resin. The resin film may be an unstretched film or a stretched film. As a stretched film, a uniaxially stretched film and a biaxially stretched film may be cited, preferably a biaxially stretched film. As a stretching method for forming a biaxially stretched film, for example, a sequential biaxial stretching method, a blow molding method, a simultaneous biaxial stretching method, etc. may be cited. As a method for coating a resin, a roll coating method, a gravure coating method, an extrusion coating method, etc. may be cited.
[0043] Examples of the resin forming the substrate layer 1 include polyester, polyamide, polyolefin, epoxy resin, acrylic resin, fluororesin, polyurethane, silicone resin, phenolic resin and the like, or modified products of these resins. In addition, the resin forming the substrate layer 1 may be a copolymer of these resins, or a modified product of a copolymer. Furthermore, it may be a mixture of these resins.
[0044] As the resin forming the base material layer 1, polyester and polyamide are preferably used among these.
[0045] As polyester, specifically, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, copolyester, etc. can be cited. In addition, as copolyester, copolyester with ethylene terephthalate as the main body of repeating unit can be cited. Specifically, copolymer polyester (hereinafter abbreviated according to the writing method of polyethylene glycol (terephthalate / isophthalate)) in which ethylene terephthalate is polymerized with ethylene isophthalate as the main body of repeating unit, polyethylene glycol (terephthalate / adipate), polyethylene glycol (terephthalate / sodium isophthalate), polyethylene glycol (terephthalate / sodium isophthalate), polyethylene glycol (terephthalate / phenyl-dicarboxylate), polyethylene glycol (terephthalate / decane dicarboxylate), etc. can be cited. These polyesters may be used alone or in combination of two or more.
[0046] In addition, specific examples of polyamides include aliphatic polyamides such as nylon 6, nylon 66, nylon 610, nylon 12, nylon 46, and copolymers of nylon 6 and nylon 66; hexamethylenediamine-isophthalic acid-terephthalic acid copolymer polyamides such as nylon 6I, nylon 6T, nylon 6IT, and nylon 6I6T (I represents isophthalic acid, and T represents terephthalic acid) containing structural units derived from terephthalic acid and / or isophthalic acid; Aromatic polyamides such as polyamide MXD6 (poly(m-xylylene adipamide)); alicyclic polyamides such as polyamide PACM6 (poly(bis(4-aminocyclohexyl)methane adipamide); polyamides obtained by copolymerizing a lactam component and an isocyanate component such as 4,4′-diphenylmethane-diisocyanate; polyesteramide copolymers or polyetheresteramide copolymers obtained by copolymerizing a polyamide with a polyester or a polyalkylene ether glycol ester; and copolymers thereof. These polyamides may be used alone or in combination of two or more.
[0047] The substrate layer 1 preferably comprises at least one of a polyester film, a polyamide film and a polyolefin film, preferably comprises at least one of a stretched polyester film, a stretched polyamide film and a stretched polyolefin film, more preferably comprises at least one of a stretched polyethylene terephthalate film, a stretched polybutylene terephthalate film, a stretched nylon film and a stretched polypropylene film, and even more preferably comprises at least one of a biaxially stretched polyethylene terephthalate film, a biaxially stretched polybutylene terephthalate film, a biaxially stretched nylon film and a biaxially stretched polypropylene film.
[0048] The substrate layer 1 may be a single layer or may be composed of two or more layers. When the substrate layer 1 is composed of two or more layers, the substrate layer 1 may be a laminated body formed by laminating resin films using an adhesive or the like, or a laminated body formed by co-extruding resins to form two or more layers of resin films. In addition, a laminated body formed by co-extruding resins to form two or more layers of resin films may be used as the substrate layer 1 in an unstretched state, or may be used as the substrate layer 1 after being uniaxially stretched or biaxially stretched.
[0049] In the substrate layer 1, as specific examples of a laminate of two or more layers of resin films, a laminate of a polyester film and a nylon film, a laminate of two or more layers of nylon films, a laminate of two or more layers of polyester films, etc. can be cited, and preferably a laminate of a stretched nylon film and a stretched polyester film, a laminate of two or more layers of stretched nylon films, and a laminate of two or more layers of stretched polyester films. For example, when the substrate layer 1 is a laminate of two layers of resin films, preferably a laminate of a polyester resin film and a polyester resin film, a laminate of a polyamide resin film and a polyamide resin film, or a laminate of a polyester resin film and a polyamide resin film, more preferably a laminate of a polyethylene terephthalate film and a polyethylene terephthalate film, a laminate of a nylon film and a nylon film, or a laminate of a polyethylene terephthalate film and a nylon film. Furthermore, since polyester resin is less likely to be discolored when, for example, an electrolyte solution adheres to its surface, when the base layer 1 is a laminate of two or more resin films, the polyester resin film is preferably located as the outermost layer of the base layer 1 .
[0050] In the case where the substrate layer 1 is a laminate of two or more layers of resin films, the two or more layers of resin films can be laminated via an adhesive. As for the preferred adhesive, the same adhesive as the adhesive exemplified in the adhesive layer 2 described later can be cited. It should be noted that there is no particular limitation on the method of laminating two or more layers of resin films, and a known method can be adopted, for example, dry lamination, sandwich lamination, extrusion lamination, thermal lamination, etc., preferably dry lamination. In the case of lamination by dry lamination, a polyurethane adhesive is preferably used as an adhesive. At this time, the thickness of the adhesive can be, for example, about 2 to 5 μm. In addition, a primer layer can be formed on the resin film and laminated. The primer layer can be the same material as the adhesive exemplified in the adhesive layer 2 described later. At this time, the thickness of the primer layer can be, for example, about 0.01 to 1.0 μm.
[0051] In addition, additives such as lubricants, flame retardants, antiblocking agents, antioxidants, light stabilizers, tackifiers, and antistatic agents may be present on at least one of the surface and the inside of the base layer 1. The additives may be used alone or in combination of two or more.
[0052] In the present invention, from the viewpoint of improving the moldability of the outer packaging material for the storage device, it is preferred that a lubricant is present on the surface of the substrate layer 1. As the lubricant, there is no particular limitation, and an amide lubricant is preferably cited. As specific examples of amide lubricants, for example, saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethyl amides, saturated fatty acid bisamides, unsaturated fatty acid bisamides, fatty acid ester amides, aromatic bisamides, etc. can be cited. As specific examples of saturated fatty acid amides, lauric acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, hydroxystearic acid amide, etc. can be cited. As specific examples of unsaturated fatty acid amides, oleic acid amide, erucic acid amide, etc. can be cited. As specific examples of substituted amides, N-oleyl palmitic acid amide, N-stearyl stearic acid amide, N-stearyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl erucic acid amide, etc. can be cited. In addition, as specific examples of hydroxymethyl amides, hydroxymethyl stearic acid amide, etc. can be cited. Specific examples of saturated fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene hydroxystearic acid amide, N,N′-distearyl adipamide, N,N′-distearyl sebacic acid amide, etc. Specific examples of unsaturated fatty acid bisamides include ethylene bisoleic acid amide, ethylene biserucic acid amide, hexamethylene bisoleic acid amide, N,N′-dioleyl adipamide, N,N′-dioleyl sebacic acid amide, etc. Specific examples of fatty acid ester amides include stearylamide ethyl stearate, etc. Specific examples of the aromatic bisamide include metaxylylene bisstearic acid amide, metaxylylene bishydroxystearic acid amide, N,N′-distearylisophthalic acid amide, etc. The lubricant may be used alone or in combination of two or more.
[0053] When a lubricant is present on the surface of the base material layer 1, the amount of the lubricant is not particularly limited, but preferably about 3 mg / m 2 The above, more preferably 4 to 15 mg / m 2 About 5 to 14 mg / m 2 about.
[0054] The lubricant present on the surface of the base layer 1 may be a lubricant seeping out from the lubricant contained in the resin constituting the base layer 1 , or may be a lubricant applied on the surface of the base layer 1 .
[0055] The thickness of the substrate layer 1 is not particularly limited as long as it can function as a substrate, and can be, for example, about 3 to 50 μm, preferably about 10 to 35 μm. When the substrate layer 1 is a laminate of two or more layers of resin films, the thickness of the resin films constituting each layer is preferably about 2 to 25 μm.
[0056] [Adhesive layer 2]
[0057] In the packaging material for a power storage device of the present invention, the adhesive layer 2 is a layer provided between the base layer 1 and the barrier layer 3 as necessary in order to improve the adhesion between them.
[0058] The adhesive layer 2 is formed of an adhesive capable of bonding the substrate layer 1 and the barrier layer 3. The adhesive used to form the adhesive layer 2 is not limited, and may be any type of chemical reaction type, solvent evaporation type, hot melt type, hot pressing type, etc. In addition, it may be a two-liquid curing adhesive (two-liquid adhesive), a single-liquid curing adhesive (single-liquid adhesive), or a resin that is not accompanied by a curing reaction. In addition, the adhesive layer 2 may be a single layer or a multilayer.
[0059] As the adhesive component contained in the adhesive, specifically, polyesters such as polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polybutylene naphthalate, polyethylene isophthalate, and copolyesters can be listed; polyethers; polyurethanes; epoxy resins; phenolic resins; polyamides such as nylon 6, nylon 66, nylon 12, and copolyamides; polyolefin resins such as polyolefins, cyclic polyolefins, acid-modified polyolefins, and acid-modified cyclic polyolefins; polyvinyl acetate; cellulose; (meth) acrylic resins; polyimides; polycarbonates; amino resins such as urea resins and melamine resins; rubbers such as chloroprene rubber, nitrile rubber, and styrene-butadiene rubber; silicone resins, etc. These adhesive components can be used alone or in combination of two or more. Among these adhesive components, polyurethane adhesives are preferably listed. In addition, the bonding strength of the resins as the bonding components can be improved by using a suitable curing agent at the same time. The curing agent can be appropriately selected from polyisocyanates, multifunctional epoxy resins, oxazoline-containing polymers, polyamine resins, acid anhydrides, etc. according to the functional groups of the bonding components.
[0060] As the polyurethane adhesive, for example, a polyurethane adhesive comprising a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. Preferably, a two-liquid curing type polyurethane adhesive is cited, which uses a polyol such as polyester polyol, polyether polyol and acrylic polyol as a main agent and an aromatic or aliphatic polyisocyanate as a curing agent. In addition, as the polyol compound, a polyester polyol having a hydroxyl group in the side chain in addition to the hydroxyl group at the end of the repeating unit is preferably used. By forming the adhesive layer 2 with a polyurethane adhesive, it is possible to impart excellent electrolyte resistance to the outer packaging material for the storage device, and even if an electrolyte is attached to the side, it is possible to suppress the peeling of the substrate layer 1.
[0061] In addition, as long as it does not hinder adhesion, other ingredients are allowed to be added to the adhesive layer 2, and colorants, thermoplastic elastomers, tackifiers, fillers, etc. may be contained. By making the adhesive layer 2 contain a colorant, the outer packaging material for the storage device can be colored. As the colorant, known substances such as pigments and dyes can be used. In addition, the colorant can be used only one kind, or two or more kinds can be mixed and used.
[0062] The type of pigment is not particularly limited as long as it does not impair the adhesiveness of the adhesive layer 2. Examples of organic pigments include azo pigments, phthalocyanine pigments, quinacridone pigments, anthraquinone pigments, dioxazine pigments, indigo thioindigo pigments, pyrenone-perylene pigments, isoindolenine pigments, benzimidazolone pigments, and the like. Examples of inorganic pigments include carbon black pigments, titanium oxide pigments, cadmium pigments, lead pigments, chromium oxide pigments, iron pigments, and fine powders of mica and fish scale foil.
[0063] Among the colorants, carbon black is preferred in order to make the appearance of the packaging material for a power storage device black, for example.
[0064] The average particle size of the pigment is not particularly limited, and is, for example, about 0.05 to 5 μm, preferably about 0.08 to 2 μm. The average particle size of the pigment is a median particle size measured by a laser diffraction / scattering particle size distribution measuring device.
[0065] The content of the pigment in the adhesive layer 2 is not particularly limited as long as the outer packaging material for a power storage device can be colored, and is, for example, about 5 to 60% by mass, preferably 10 to 40% by mass.
[0066] The thickness of the adhesive layer 2 is not particularly limited as long as the base layer 1 and the barrier layer 3 can be bonded, and is, for example, about 1 μm or more, about 2 μm or more. In addition, the thickness of the adhesive layer 2 is, for example, about 10 μm or less, about 5 μm or less. The preferred range of the thickness of the adhesive layer 2 is about 1 to 10 μm, about 1 to 5 μm, about 2 to 10 μm, and about 2 to 5 μm.
[0067] [Coloring Layer]
[0068] The colored layer is a layer (not shown) provided as needed between the base layer 1 and the barrier layer 3. In the case of having an adhesive layer 2, the colored layer may be provided between the base layer 1 and the adhesive layer 2, or between the adhesive layer 2 and the barrier layer 3. In addition, the colored layer may be provided outside the base layer 1. By providing the colored layer, the outer packaging material for the power storage device can be colored.
[0069] The colored layer can be formed, for example, by applying ink containing a colorant to the surface of the base layer 1 or the surface of the barrier layer 3. As the colorant, known substances such as pigments and dyes can be used. In addition, the colorant can be used alone or in combination of two or more.
[0070] Specific examples of the colorant contained in the colored layer include the same ones as those exemplified in the section of [Adhesive Layer 2].
[0071] [Barrier layer 3]
[0072] In the packaging material for a power storage device, the barrier layer 3 is a layer that at least suppresses the intrusion of moisture.
[0073] As the barrier layer 3, for example, metal foil, vapor-deposited film, resin layer, etc. having barrier properties can be listed. As the vapor-deposited film, metal vapor-deposited film, inorganic oxide vapor-deposited film, carbon-containing inorganic oxide vapor-deposited film, etc. can be listed. As the resin layer, polyvinylidene chloride, polymers with chlorotrifluoroethylene (CTFE) as the main component or polymers with tetrafluoroethylene (TFE) as the main component, polymers with fluoroalkyl groups, and polymers with fluorocarbon units as the main component, etc., fluorine-containing resins, ethylene vinyl alcohol copolymers, etc. can be listed. In addition, as the barrier layer 3, a resin film provided with at least one layer of these vapor-deposited films and resin layers can be listed. The barrier layer 3 can be provided with multiple layers. The barrier layer 3 preferably includes a layer composed of a metal material. As the metal material constituting the barrier layer 3, specifically, aluminum alloy, stainless steel, titanium steel, steel plate, etc. can be listed. When used as a metal foil, it is preferably included at least one of aluminum alloy foil and stainless steel foil.
[0074] Regarding the aluminum alloy foil, from the viewpoint of improving the formability of the outer packaging material for the power storage device, for example, a soft aluminum alloy foil composed of an annealed aluminum alloy or the like is more preferred, and from the viewpoint of further improving the formability, an aluminum alloy foil containing iron is preferred. In the aluminum alloy foil containing iron (100% by mass), the iron content is preferably 0.1 to 9.0% by mass, and more preferably 0.5 to 2.0% by mass. By making the iron content above 0.1% by mass, an outer packaging material for a power storage device with better formability can be obtained. By making the iron content below 9.0% by mass, an outer packaging material for a power storage device with better flexibility can be obtained. As soft aluminum alloy foil, for example, aluminum alloy foil having a composition specified in JIS H4160: 1994A8021H-O, JIS H4160: 1994A8079H-O, JIS H4000: 2014A8021P-O, or JIS H4000: 2014A8079P-O can be cited. In addition, silicon, magnesium, copper, manganese, etc. may be added as needed. In addition, softening can be performed by annealing treatment or the like.
[0075] In addition, examples of stainless steel foil include austenitic, ferritic, austenite-ferritic, martensitic, and precipitation-hardened stainless steel foils. In addition, from the perspective of providing an outer packaging material for a power storage device having excellent formability, the stainless steel foil is preferably made of austenitic stainless steel.
[0076] Specific examples of the austenitic stainless steel constituting the stainless steel foil include SUS304, SUS301, and SUS316L. Among these, SUS304 is particularly preferred.
[0077] Regarding the thickness of the barrier layer 3, in the case of a metal foil, as long as it can play a function as a barrier layer that at least inhibits the infiltration of water, for example, about 9 to 200 μm can be cited. The thickness of the barrier layer 3 is preferably about 85 μm or less, more preferably about 50 μm or less, more preferably about 40 μm or less, and particularly preferably about 35 μm or less. In addition, the thickness of the barrier layer 3 is preferably about 10 μm or more, more preferably about 20 μm or more, and more preferably about 25 μm or more. As a preferred range of the thickness, about 10 to 85 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 35 μm, about 20 to 85 μm, about 20 to 50 μm, about 20 to 40 μm, about 20 to 35 μm, about 25 to 85 μm, about 25 to 50 μm, about 25 to 40 μm, and about 25 to 35 μm. When the barrier layer 3 is composed of an aluminum alloy foil, the above range is particularly preferred. In addition, in particular, when the barrier layer 3 is composed of a stainless steel foil, the thickness of the stainless steel foil is preferably about 60 μm or less, more preferably about 50 μm or less, more preferably about 40 μm or less, more preferably about 30 μm or less, and particularly preferably about 25 μm or less. In addition, the thickness of the stainless steel foil is preferably about 10 μm or more, and more preferably about 15 μm or more. In addition, as the preferred thickness range of the stainless steel foil, about 10 to 60 μm, about 10 to 50 μm, about 10 to 40 μm, about 10 to 30 μm, about 10 to 25 μm, about 15 to 60 μm, about 15 to 50 μm, about 15 to 40 μm, about 15 to 30 μm, and about 15 to 25 μm can be listed.
[0078] In addition, when the barrier layer 3 is a metal foil, in order to prevent dissolution, corrosion, etc., it is preferred that at least the surface on the opposite side of the substrate layer has a corrosion-resistant film. The barrier layer 3 may also have a corrosion-resistant film on both surfaces. Among them, the corrosion-resistant film refers to, for example, a corrosion-resistant film made by subjecting the surface of the barrier layer to hot water modification treatment such as boehm film treatment, chemical surface treatment, anodizing treatment, plating treatment such as nickel or chromium, and anti-corrosion treatment by coating a coating agent to make the barrier layer have corrosion resistance. As a treatment for forming a corrosion-resistant film, one type can be performed, or two or more types can be combined. In addition, not just one layer, but multiple layers can also be used. Further, among these treatments, hot water modification treatment and anodizing treatment are treatments that use a treatment agent to dissolve the surface of the metal foil to form a metal compound with excellent corrosion resistance. In addition, these treatments are sometimes also included in the definition of chemical surface treatment. In addition, when the barrier layer 3 has a corrosion-resistant film, the corrosion-resistant film is included as the barrier layer 3.
[0079] The corrosion-resistant film exhibits the following effects during the molding of the outer packaging material for the storage device: preventing delamination between the barrier layer (e.g., aluminum alloy foil) and the substrate layer; preventing the surface of the barrier layer from being dissolved and corroded by hydrogen fluoride generated by the reaction of the electrolyte and water, especially when the barrier layer is an aluminum alloy foil, preventing the aluminum oxide present on the surface of the barrier layer from being dissolved and corroded; and improving the adhesion (wettability) of the barrier layer surface; preventing delamination of the substrate layer and the barrier layer during heat sealing; and preventing delamination of the substrate layer and the barrier layer during molding.
[0080] As corrosion-resistant films formed by chemical surface treatment, various films are known, mainly including corrosion-resistant films containing at least one of phosphates, chromates, fluorides, triazine thiol compounds and rare earth oxides. As chemical surface treatment using phosphates and chromates, for example, chromic acid chromate treatment, phosphoric acid chromate treatment, phosphoric acid-chromate treatment, chromate treatment, etc. can be listed, and as chromium compounds used for these treatments, for example, chromium nitrate, chromium fluoride, chromium sulfate, chromium acetate, chromium oxalate, chromium dihydrogen phosphate, chromic acid acetoacetate, chromium chloride, potassium chromium sulfate, etc. can be listed. In addition, as phosphorus compounds used for these treatments, sodium phosphate, potassium phosphate, ammonium phosphate, polyphosphoric acid, etc. can be listed. In addition, as chromate treatment, etching chromate treatment, electrolytic chromate treatment, coating type chromate treatment, etc. can be listed, and coating type chromate treatment is preferred. The coating type chromate treatment is a treatment as follows: first, degreasing the surface of at least the inner layer side of the barrier layer (for example, aluminum alloy foil) by a known treatment method such as alkali immersion, electrolytic cleaning, acid cleaning, electrolytic acid cleaning, acid activation, etc., and then coating the degreased surface with a treatment liquid containing a phosphate metal salt such as Cr (chromium) phosphate, Ti (titanium) phosphate, Zr (zirconium) phosphate, Zn (zinc) phosphate and a mixture of these metal salts, or a treatment liquid containing a phosphate nonmetallic salt and a mixture of these nonmetallic salts, or a treatment liquid composed of a mixture of these and a synthetic resin, etc., by a known coating method such as roll coating, gravure printing, dipping, etc., and then drying. The treatment liquid can use various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, ether solvents, etc., preferably water. In addition, as the resin component used at this time, polymers such as phenolic resins and acrylic resins can be listed, and chromate treatment using an aminophenolic polymer having repeating units represented by the following general formulas (1) to (4) can be listed. It should be noted that in the aminophenol polymer, the repeating units represented by the general formulas (1) to (4) described below can contain a single type or any combination of two or more types. The acrylic resin is preferably polyacrylic acid, acrylic acid methacrylate copolymer, acrylic acid maleic acid copolymer, acrylic acid styrene copolymer, or their sodium salts, ammonium salts, amine salts and other derivatives. Particularly preferred are derivatives of polyacrylic acid such as ammonium salts, sodium salts, or amine salts of polyacrylic acid. In the present invention, polyacrylic acid refers to a polymer of acrylic acid. In addition, the acrylic resin is preferably a copolymer of acrylic acid and a dicarboxylic acid or a dicarboxylic anhydride, and is also preferably an ammonium salt, sodium salt or amine salt of a copolymer of acrylic acid and a dicarboxylic acid or a dicarboxylic anhydride. The acrylic resin can be used alone or in combination of two or more.
[0081]
[0082] In the general formulae (1) to (4), X represents a hydrogen atom, a hydroxyl group, an alkyl group, a hydroxyalkyl group, an allyl group or a benzyl group. 1 and R 2 are the same or different and represent hydroxyl, alkyl or hydroxyalkyl. 1 and R 2 The alkyl group represented by , for example, can be a linear or branched alkyl group having 1 to 4 carbon atoms, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, and tert-butyl. 1 and R 2 The hydroxyalkyl group represented by the above-mentioned group includes, for example, hydroxymethyl, 1-hydroxyethyl, 2-hydroxyethyl, 1-hydroxypropyl, 2-hydroxypropyl, 3-hydroxypropyl, 1-hydroxybutyl, 2-hydroxybutyl, 3-hydroxybutyl, 4-hydroxybutyl, and other linear or branched alkyl groups having 1 to 4 carbon atoms substituted with one hydroxy group. 1 and R 2 The alkyl and hydroxyalkyl groups shown may be the same or different. In the general formulas (1) to (4), X is preferably a hydrogen atom, a hydroxyl group or a hydroxyalkyl group. The number average molecular weight of the aminophenol polymer having the repeating units shown in the general formulas (1) to (4) is, for example, preferably about 5 to 1,000,000, and more preferably about 1,000 to 20,000. The aminophenol polymer can be produced, for example, by the following method: a phenol compound or a naphthol compound is condensed with formaldehyde to produce a polymer containing the repeating units shown in the general formula (1) or (3), and then, using formaldehyde and an amine (R 1 R 2 NH) will be functional group (-CH2NR 1 R 2 ) is introduced into the polymer obtained above. The aminated phenol polymer may be used alone or in combination of two or more.
[0083] As other examples of corrosion-resistant films, films formed by coating-type anti-corrosion treatment by applying a coating agent containing at least one selected from rare earth oxide sol, anionic polymers, and cationic polymers can be cited. The coating agent can also contain phosphoric acid or phosphate, and a cross-linking agent for cross-linking the polymer. In the rare earth oxide sol, microparticles of rare earth oxide (for example, particles with an average particle size of less than 100 nm) are dispersed in a liquid dispersion medium. As rare earth oxides, cerium oxide, yttrium oxide, neodymium oxide, lanthanum oxide, etc. can be cited. From the perspective of further improving adhesion, cerium oxide is preferred. The rare earth oxides contained in the corrosion-resistant film can be used alone or in combination of two or more. As the liquid dispersion medium of the rare earth oxide sol, various solvents such as water, alcohol solvents, hydrocarbon solvents, ketone solvents, ester solvents, and ether solvents can be used, preferably water. As cationic polymers, for example, polyethyleneimine, ionic polymer coordination compounds formed by polyethyleneimine and polymers having carboxylic acids, primary amine grafted acrylic resins formed by graft polymerization of primary amines and acrylic acid main skeletons, polyallylamine or its derivatives, aminophenols, etc. are preferred. In addition, as anionic polymers, poly(methyl)acrylic acid or its salts, or copolymers with (methyl)acrylic acid or its salts as main components are preferred. In addition, the crosslinking agent is preferably selected from at least one of a compound having any functional group among isocyanate group, glycidyl group, carboxyl group, oxazoline group and a silane coupling agent. In addition, the above-mentioned phosphoric acid or phosphate is preferably condensed phosphoric acid or condensed phosphate.
[0084] An example of a corrosion-resistant film is a film formed by dispersing fine particles of a metal oxide such as aluminum oxide, titanium oxide, cerium oxide, tin oxide, or barium sulfate in phosphoric acid, applying the resulting dispersion to the surface of the barrier layer, and baking the dispersion at 150° C. or higher.
[0085] If necessary, the corrosion-resistant film may be formed into a laminated structure in which at least one of a cationic polymer and an anionic polymer is further laminated. Examples of the cationic polymer and the anionic polymer include the above-mentioned polymers.
[0086] Here, the composition analysis of the corrosion-resistant film can be performed by, for example, time-of-flight secondary ion mass spectrometry.
[0087] There is no particular limitation on the amount of the corrosion-resistant film formed on the surface of the barrier layer 3 in the chemical reaction surface treatment. For example, in the case of a coating-type chromate treatment, it is desirable to form a corrosion-resistant film on the surface of the barrier layer 3 by 1 m2. 2On the surface, the content ratio of the chromic acid compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as chromium; the content ratio of the phosphorus compound is, for example, about 0.5 to 50 mg, preferably about 1.0 to 40 mg, calculated as phosphorus; and the content ratio of the aminophenolic polymer is, for example, about 1.0 to 200 mg, preferably about 5.0 to 150 mg.
[0088] There is no particular limitation on the thickness of the corrosion-resistant film. From the perspective of the cohesive force of the film and the adhesion with the barrier layer or the heat-fusible resin layer, a thickness of about 1 nm to 20 μm is preferred, about 1 nm to 100 nm is more preferred, and about 1 nm to 50 nm is further preferred. It should be noted that the thickness of the corrosion-resistant film can be measured by observation using a transmission electron microscope or by combining observation using a transmission electron microscope with energy dispersive X-ray spectroscopy or electron beam energy loss spectroscopy. By analyzing the composition of the corrosion-resistant film using time-of-flight secondary ion mass spectrometry, secondary ions (e.g., Ce2PO4 + 、CePO4 - At least one of the above), for example, secondary ions composed of Cr, P and O (such as CrPO2 + 、CrPO4 - At least one of the above (etc.) peaks.
[0089] After applying a solution containing a compound for forming a corrosion-resistant film to the surface of the barrier layer by a rod coating method, a roller coating method, a gravure coating method, a dipping method, etc., the temperature of the barrier layer is heated to about 70 to 200°C, thereby performing a chemical surface treatment. In addition, before the barrier layer is subjected to a chemical surface treatment, the barrier layer may be degreased in advance by an alkali immersion method, an electrolytic cleaning method, an acid cleaning method, an electrolytic acid cleaning method, etc. By performing such a degreasing treatment, the surface of the barrier layer can be further efficiently chemically treated. In addition, by using an acid degreasing agent obtained by dissolving a fluorine-containing compound in an inorganic acid in the degreasing treatment, not only the degreasing effect of the metal foil can be achieved, but also a passive metal fluoride can be formed. In this case, only the degreasing treatment may be performed.
[0090] [Thermal Fusible Resin Layer 4]
[0091] In the packaging material for a power storage device of the present invention, the heat-fusible resin layer 4 corresponds to the innermost layer and is a layer (sealing layer) that performs the function of sealing the power storage device element by heat-fusion bonding the heat-fusible resin layers when assembling the power storage device.
[0092] The heat-fusible resin layer 4 contains polypropylene and polyethylene. In the outer packaging material for a power storage device of the present invention, a cross-sectional image of the heat-fusible resin layer 4 in a direction parallel to TD and in the thickness direction y is obtained using a scanning electron microscope to observe a sea-island structure. Figure 3 As shown in the schematic diagram of FIG. 1 , when the total thickness of the layers located inside the barrier layer 3 is set to 100%, the range from the surface of the heat-fusible resin layer 4 on the side opposite to the barrier layer 3 to the portion with a thickness of 12.5% ( Figure 3 The cross-sectional image obtained by the area surrounded by the dotted line (the area surrounded by the dotted line). The surface of the heat-fusible resin layer 4 on the opposite side to the barrier layer 3 side has a thickness of 0%. To explain with a specific example, as in Examples 1 and 2 described later, in the outer packaging material for a storage device in which a base material layer (including a thickness of 30 μm of an adhesive) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-fusible resin layer (40 μm) are sequentially laminated, the layers located on the inner side of the barrier layer 3 are the adhesive layer (40 μm) and the heat-fusible resin layer (40 μm), and their total thickness of 80 μm is set to 100%. In addition, the position of the surface of the heat-fusible resin layer 4 on the opposite side to the barrier layer 3 side refers to the inner surface (inner surface) of the outer packaging material 10 for a storage device, and the thickness of this position is set to 0%. Furthermore, a cross-sectional image is obtained using a scanning electron microscope in the range from the surface (0% thickness) to the position of 12.5% thickness (i.e., taking a total of 80 μm as 100%, the position of 12.5% thickness is the position from the surface of the thermally fusible resin layer 4 on the opposite side of the barrier layer 3 to the position where the thickness toward the barrier layer 3 reaches 10 μm).
[0093] The observation of the sea-island structure in the cross-sectional image means that the sea portion (sea portion) and the island portion (island portion) are observed in the cross-sectional image. As described above, when a small amount of polyethylene is added to polypropylene and a heat-fusible resin layer is formed by melt extrusion molding, a sea-island structure is formed in which the island portions of polyethylene are dispersed in the sea portion of polypropylene. It should be noted that in order to observe the sea-island structure, as described later, the cross-section of the heat-fusible resin layer is stained with ruthenium tetroxide or the like, and the cross-sectional image is obtained using a scanning electron microscope and then observed.
[0094] In the outer packaging material for a power storage device of the present invention, in the cross-sectional image of the heat-fusible resin layer 4, the area of the island portions is 0.02 μm with respect to the total number of island portions of the sea-island structure. 2The total number of the following islands accounts for 80.0% or more. The outer packaging material for a storage device of the present invention has such a feature that the whitening of the heat-fusible resin layer caused by cold forming of the outer packaging material for a storage device and the reduction in the insulation of the outer packaging material for a storage device are suppressed. That is, in the outer packaging material for a storage device of the present invention, in the heat-fusible resin layer 4 containing polypropylene and polyethylene, among all the islands, the area of 0.02 μm 2 The proportion of such very fine island portions is set to be relatively high, thereby effectively suppressing the generation of fine cracks at the interface between the polypropylene portion and the polyethylene portion of the heat-fusible resin layer. As a result, it can be considered that the whitening of the heat-fusible resin layer 4 and the reduction in the insulation properties of the outer packaging material for the storage device caused by cold forming of the outer packaging material for the storage device are suppressed.
[0095] In the cross-sectional image of the thermally adhesive resin layer 4, the area of the island portions is 0.02 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of islands below (0.02 μm 2 The total number of islands below / the total number of all islands) is 80.0% or more. From the viewpoint of more effectively suppressing the above-mentioned whitening and reduction in insulation, it is preferably 90.0% or more, and more preferably 95.0% or more. Among them, the ratio of the total number is, for example, 100.0% or less, 99.0% or less, or 98.0% or less. As the preferred range of the ratio of the total number, for example, about 80.0 to 100.0%, about 80.0 to 99.0%, about 80.0 to 98.0%, about 90.0 to 100.0%, about 90.0 to 99.0%, about 90.0 to 98.0%, about 95.0 to 100.0%, about 95.0 to 99.0%, and about 95.0 to 98.0% can be listed.
[0096] In order to more effectively suppress the above-mentioned whitening and reduction in insulation, in the cross-sectional image of the heat-fusible resin layer 4, the area of the island portion is 0.01 μm relative to the total number of island portions of the sea-island structure. 2 The ratio of the total number of islands below (0.01 μm 2The total number of islands below / the total number of all islands) is preferably 50.0% or more, more preferably 55.0% or more, and even more preferably 60.0% or more. Among them, the ratio of the total number is, for example, 80.0% or less, 75.0% or less, 70.0% or less, etc. As the preferred range of the ratio of the total number, for example, about 50.0-80.0%, about 50.0-75.0%, about 50.0-70.0%, about 55.0-80.0%, about 55.0-75.0%, about 55.0-70.0%, about 60.0-80.0%, about 60.0-75.0%, about 60.0-70.0%.
[0097] In order to more effectively suppress the above-mentioned whitening and reduction in insulation, in the cross-sectional image of the heat-fusible resin layer 4, the area of the island portion is 0.03 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of islands below (0.03 μm 2 The total number of islands below / the total number of all islands) is preferably 90.0% or more, more preferably 95.0% or more, and even more preferably 97.0% or more. Among them, the ratio of the total number is, for example, 100.0% or less, 99.0% or less, 98.0% or less, etc. As the preferred range of the ratio of the total number, for example, about 90.0 to 100.0%, about 90.0 to 99.0%, about 90.0 to 98.0%, about 95.0 to 100.0%, about 95.0 to 99.0%, about 95.0 to 98.0%, about 97.0 to 100.0%, about 97.0 to 99.0%, and about 97.0 to 98.0% can be listed.
[0098] In order to more effectively suppress the above-mentioned whitening and reduction in insulation, in the cross-sectional image of the heat-fusible resin layer 4, the area of the island portion is 0.30 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of islands above 0.30 μm 2 The total number of island portions / the total number of all island portions) is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. The ratio of the total number is, for example, 0.0% or more.
[0099] In order to more effectively suppress the above-mentioned whitening and reduction in insulation, in the cross-sectional image of the heat-fusible resin layer 4, the area of the island portion is 0.15 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of islands above 0.15 μm 2The total number of island portions / the total number of all island portions) is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. The ratio of the total number is, for example, 0.0% or more.
[0100] In addition, from the viewpoint of more effectively suppressing the above-mentioned whitening and reduction in insulation, in the cross-sectional image of the thermally fusible resin layer 4, the ratio of the total area of the island portions of the sea-island structure to the area of the measurement range of the cross-sectional image (total area of the island portions / area of the measurement range of the cross-sectional image) is preferably 12.0% or less, more preferably 5.0% or less, and even more preferably 1.0% or less. The ratio of the total area may be, for example, 0.1% or more. The preferred range of the ratio of the total area may be, for example, about 0.1 to 12.0%, about 0.1 to 5.0%, or about 0.1 to 1.0%.
[0101] Regarding the ratio of the total area of the island portions of the above-mentioned areas, in addition to the mixing ratio of polypropylene and polyethylene contained in the heat-fusible resin layer 4, the above-mentioned value can also be achieved by adjusting the conditions when the heat-fusible resin layer 4 is formed (for example, when the heat-fusible resin layer 4 is formed by melt extrusion molding as described later, the cooling condition of the heat-fusible resin layer using a cooling roller is set to a sudden cooling condition (for example, the difference between the surface temperature of the melt-extruded heat-fusible resin layer and the cooling roller is set to 70°C or more), thereby suppressing the crystal growth of polyethylene in the polypropylene).
[0102] The method of measuring the ratio of the area of the island portion in the sea-island structure with respect to the cross-sectional image of the thermally adhesive resin layer 4 is as follows.
[0103] <Measurement of the ratio between the area and number of islands in a sea-island structure>
[0104] The outer packaging material for the storage device is embedded in a thermosetting epoxy resin and cured. A commercially available rotary ultrathin slicer (e.g., EMUC6 manufactured by LEICA) and a glass knife are used to make a section parallel to TD and in the thickness direction y. At this time, a room temperature ultrathin slicer is used to make the section. The heat-fusible resin layer of the outer packaging material for the storage device together with the embedding resin is stained with ruthenium tetroxide for 3 hours. After staining, the resin swells and the island structure cannot be confirmed near the section, so the swollen part is trimmed using an ultrathin slicer. After that, a diamond knife is used to sample the section after cutting off about 1μm to 2μm, and the stained section with a thickness of about 100nm is observed in the following manner. For the stained section, a field emission scanning electron microscope (e.g., S-4800 manufactured by Hitachi High-Tech Co., Ltd.) is used to obtain a cross-sectional image. It should be noted that, as described above, the cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to the portion of 12.5% thickness, when the total thickness of the layers located on the inner side of the barrier layer is set to 100%. As a field emission scanning electron microscope, when using, for example, Hitachi High-Technologies Corporation S-4800, the measurement conditions are set as: acceleration voltage: 30 kV, emission current: 10 μA, detector: transmission detector, tilt: none (0°), observation magnification 5000 times. Afterwards, the cross-sectional image is binarized using image processing software capable of binarization (for example, image analysis software attached to Keyence electron microscope VHX-5000) to binarize the island part and the sea part of the sea island structure. As image processing software, for example, when using the image analysis software included with the Keyence electron microscope VHX-5000, specifically, the measurement can be started under the brightness (standard) condition of the image analysis software, and the extraction area (measurement range) is set to a rectangle (7 μm in length and 13 μm in width), the shooting size is set to standard (1600×1200), the tilt angle is set to 0 degrees, the shooting mode is set to normal shooting, and the extraction object is a "dark area". In addition, through automatic measurement, the parts that cannot be extracted and the redundant extractions are corrected, and the total area and total number of the extracted positions (islands) are measured. At this time, the area and number of all islands present in the extraction area are measured separately. Using the acquired data, the ratio of the total area of all islands to the area of the measurement range of the cross-sectional image is calculated (total area of islands / area of the measurement range of the cross-sectional image), and the area of all islands is 0.01 μm 2 The ratio of the total number of islands below (0.01 μm 2 The total number of islands below / the total number of all islands), 0.02 μm 2 The ratio of the total number of islands below (0.02 μm 2The total number of islands below / the total number of all islands), 0.03 μm 2 The ratio of the total number of islands below (0.03 μm 2 The total number of islands below / the total number of all islands), 0.30 μm 2 The ratio of the total number of islands above 0.30 μm 2 The total number of islands above / the total number of all islands), 0.15 μm 2 The ratio of the total number of islands above 0.15 μm 2 The total number of the above islands / the total number of all islands).
[0105] Examples of propylene include homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene, block copolymers of propylene and butene, block copolymers of propylene, ethylene and butene, preferably block copolymers of propylene and ethylene), random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene, random copolymers of propylene and butene, random copolymers of propylene, ethylene and butene, preferably random copolymers of propylene and ethylene), and propylene-α-olefin copolymers. In addition, examples of ethylene include low-density polyethylene, medium-density polyethylene, high-density polyethylene, linear low-density polyethylene, and ethylene-α-olefin copolymers. The polypropylene and polyethylene contained in the heat-fusible resin layer 4 may be either one or two or more.
[0106] The heat-fusible resin layer 4 is preferably formed of a polypropylene resin composition containing 45% by mass or less of polyethylene. The content of polyethylene in the heat-fusible resin layer 4 is adjusted so that, in the above cross-sectional image, the area of the island portion is 0.02 μm with respect to the total number of island portions of the sea-island structure. 2The ratio of the total number of islands below is 80.0% or more. The content of polyethylene is, for example, about 45% by mass or less, preferably about 30% by mass or less, more preferably about 20% by mass or less, and preferably about 5% by mass or more, more preferably about 10% by mass or more, and as a preferred range, about 5 to 45% by mass, about 5 to 30% by mass, about 5 to 20% by mass, about 10 to 45% by mass, about 10 to 30% by mass, about 10 to 20% by mass can be cited. In addition, the content of polypropylene is, for example, 95% by mass or less, 90% by mass or less. In addition, the content of polypropylene is, for example, 55% by mass or more, 70% by mass or more, and 80% by mass or more. As a preferred range of the content of polypropylene, about 55% to 95% by mass, about 70% to 95% by mass, about 80% to 95% by mass, about 55% to 90% by mass, about 70% to 90% by mass, and about 80% to 90% by mass can be cited. The mass ratio of polypropylene to polyethylene in the polypropylene resin composition is preferably about 5 to 80 parts by mass, more preferably about 5 to 45 parts by mass, and even more preferably about 10 to 30 parts by mass of polyethylene per 100 parts by mass of polypropylene.
[0107] The heat-adhesive resin layer 4 may contain other resins in addition to polypropylene and polyethylene. Examples of other resins include acid-modified polyolefins.
[0108] The acid-modified polyolefin refers to a polymer obtained by modifying a polyolefin by block polymerization or graft polymerization with an acid component.
[0109] As the acid-modified polyolefin, specifically, polyethylenes such as low-density polyethylene, medium-density polyethylene, high-density polyethylene, and linear low-density polyethylene can be listed; ethylene-α-olefin copolymers; polypropylenes such as homopolypropylene, block copolymers of polypropylene (e.g., block copolymers of propylene and ethylene), and random copolymers of polypropylene (e.g., random copolymers of propylene and ethylene); propylene-α-olefin copolymers; terpolymers of ethylene-butene-propylene, etc. Among these, polypropylene is preferred. The polyolefin resin in the case of a copolymer may be a block copolymer or a random copolymer. These polyolefin-based resins may be used alone or in combination of two or more.
[0110] In addition, the acid-modified polyolefin may also be a copolymer obtained by copolymerizing the above-mentioned polyolefin with a polar molecule such as acrylic acid or methacrylic acid, or a polymer such as a crosslinked polyolefin. In addition, as the acid component used for acid modification, for example, carboxylic acids or anhydrides thereof such as maleic acid, acrylic acid, itaconic acid, crotonic acid, maleic anhydride, and itaconic anhydride may be cited.
[0111] The acid-modified polyolefin may also be an acid-modified cyclic polyolefin. The acid-modified cyclic polyolefin may be a polymer obtained by replacing a part of the monomers constituting the cyclic polyolefin with an acid component for copolymerization, or by block polymerization or graft polymerization of the acid component to the cyclic polyolefin. For the acid-modified cyclic polyolefin, it is the same as above. In addition, the acid component used for the acid-modified cyclic polyolefin may be the same as the acid component used in the above-mentioned polyolefin modification.
[0112] Preferred examples of the acid-modified polyolefin include polyolefins modified with carboxylic acid or its anhydride, polypropylene modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polypropylene.
[0113] The thermally adhesive resin layer 4 may be formed of only one layer, or may be formed of two or more layers made of the same or different resins.
[0114] In addition, the heat-fusible resin layer 4 may contain a lubricant or the like as needed. When the heat-fusible resin layer 4 contains a lubricant, the moldability of the outer packaging material for the storage device can be improved. There is no particular limitation on the lubricant, and a known lubricant can be used. One lubricant may be used alone, or two or more lubricants may be used in combination.
[0115] The lubricant is not particularly limited, but preferably an amide lubricant is used. Specific examples of the lubricant include the lubricants exemplified for the base material layer 1. The lubricant may be used alone or in combination of two or more.
[0116] When a lubricant is present on the surface of the heat-fusible resin layer 4, the amount thereof is not particularly limited, but is preferably 10 to 50 mg / m 2 About 15 to 40 mg / m 2 about.
[0117] The lubricant present on the surface of the thermally adhesive resin layer 4 may be the lubricant that oozes out from the resin constituting the thermally adhesive resin layer 4 , or the lubricant that is applied to the surface of the thermally adhesive resin layer 4 .
[0118] In addition, the thickness of the heat-fusible resin layer 4 is not particularly limited as long as the function of heat-fusible resin layers being heat-fused to each other to seal the storage device element can be exerted, and for example, it can be about 100 μm or less, preferably about 85 μm or less, and more preferably about 15 to 85 μm. It should be noted that, for example, when the thickness of the adhesive layer 5 described later is 10 μm or more, the thickness of the heat-fusible resin layer 4 is preferably about 85 μm or less, and more preferably about 15 to 45 μm. For example, when the thickness of the adhesive layer 5 described later is less than 10 μm or when the adhesive layer 5 is not provided, the thickness of the heat-fusible resin layer 4 is preferably about 20 μm or more, and more preferably about 35 to 85 μm.
[0119] The heat-fusible resin layer 4 is preferably formed by melt extrusion molding. In addition, in the case of having an adhesive layer 5 described later, the adhesive layer 5 and the heat-fusible resin layer 4 are preferably formed by melt co-extrusion molding. In the present invention, it is preferred that the cooling condition of the molten resin forming the heat-fusible resin layer 4 is set to a quenching condition to suppress the crystal growth of polyethylene in the polypropylene, thereby making it possible to reduce the area of the island portion in the cross-sectional image to 0.02 μm. 2 The total number of the following island portions is adjusted to a ratio of 80.0% or more to the total number of the island portions of the sea island structure. For example, as described above, the mixing ratio of polypropylene and polyethylene contained in the heat-melting resin layer 4 can be appropriately adjusted, and the cooling conditions of the molten resin (molten resin forming the heat-melting resin layer) using a cooling roller (a roller that cools while conveying a sheet formed of molten resin) when the heat-melting resin layer 4 is formed by melt extrusion molding or the like are set to rapid cooling conditions (for example, by setting the difference between the surface temperature of the melt-extruded heat-melting resin layer and the surface temperature of the cooling roller to 70°C or more, etc.), thereby suppressing the crystal growth of polyethylene in the polypropylene, thereby suppressing the crystal growth of polyethylene in the island portion with an area of 0.02 μm in the above-mentioned cross-sectional image. 2 The ratio of the total number of the following island portions to the total number of the island portions of the sea-island structure is adjusted to be 80.0% or more. When the adhesive layer 5 and the heat-fusible resin layer 4 are formed by melt co-extrusion molding, it is preferred that the thickness of the adhesive layer 5 is set to 15 to 45 μm, and the thickness of the heat-fusible resin layer 4 is set to 15 to 45 μm.
[0120] [Adhesive layer 5]
[0121] In the packaging material for a power storage device of the present invention, the adhesive layer 5 is a layer provided between the barrier layer 3 (or the acid-resistant film) and the heat-fusible resin layer 4 as necessary in order to firmly adhere them.
[0122] The adhesive layer 5 is formed of a resin that can bond the barrier layer 3 to the thermally fusible resin layer 4. As the resin used to form the adhesive layer 5, for example, the same resin as the adhesive exemplified in the adhesive layer 2 can be used. It should be noted that the resin used to form the adhesive layer 5 preferably contains a polyolefin skeleton, and the polyolefins and acid-modified polyolefins exemplified in the thermally fusible resin layer 4 mentioned above can be listed. Whether the resin constituting the adhesive layer 5 contains a polyolefin skeleton can be analyzed by, for example, infrared spectroscopy, gas chromatography-mass spectrometry, etc., and the analysis method is not particularly limited. In addition, when the resin constituting the adhesive layer 5 is analyzed by infrared spectroscopy, it is preferred to detect a peak derived from maleic anhydride. For example, when maleic anhydride-modified polyolefin is measured by infrared spectroscopy, at a wave number of 1760cm -1 Nearby and wave number 1780cm -1 A peak derived from maleic anhydride is detected near the 200 nm region. However, if the degree of acid modification is low, the peak may become smaller and undetectable. In this case, analysis can be performed using nuclear magnetic resonance spectroscopy.
[0123] The adhesive layer 5 preferably contains an acid-modified polyolefin from the viewpoint of firmly bonding the barrier layer 3 and the heat-fusible resin layer 4. As the acid-modified polyolefin, polyolefin modified with carboxylic acid or its anhydride, polypropylene modified with carboxylic acid or its anhydride, maleic anhydride-modified polyolefin, and maleic anhydride-modified polypropylene are particularly preferred.
[0124] In addition, from the viewpoint of reducing the thickness of the outer packaging material for a storage device and providing an outer packaging material for a storage device with excellent shape stability after the treadle molding, a cured product of a resin composition containing an acid-modified polyolefin and a curing agent is more preferably used in the adhesive layer 5. As the acid-modified polyolefin, the above-mentioned substances can be preferably exemplified.
[0125] In addition, the adhesive layer 5 is preferably a cured product of a resin composition comprising an acid-modified polyolefin and at least one selected from a compound having an isocyanate group, a compound having an oxazoline group, and a compound having an epoxy group, and is particularly preferably a cured product of a resin composition comprising an acid-modified polyolefin and at least one selected from a compound having an isocyanate group and a compound having an epoxy group. In addition, the adhesive layer 5 preferably comprises at least one selected from polyurethane, polyester, and epoxy resin, and more preferably comprises polyurethane and epoxy resin. As polyester, for example, amide resin is preferred. Amide resin is generally generated by the reaction of a carboxyl group with an oxazoline group. The adhesive layer 5 is more preferably a cured product of a resin composition comprising at least one of these resins and the above-mentioned acid-modified polyolefin. It should be noted that when there are unreacted products of curing agents such as compounds having an isocyanate group, compounds having an oxazoline group, and epoxy resins remaining in the adhesive layer 5, the presence of the unreacted products can be confirmed by methods such as infrared spectroscopy, Raman spectroscopy, and time-of-flight secondary ion mass spectrometry (TOF-SIMS).
[0126] In addition, from the viewpoint of further improving the adhesion between the barrier layer 3 and the adhesive layer 5, the adhesive layer 5 is preferably a cured product of a resin composition containing a curing agent selected from at least one of an oxygen atom, a heterocycle, a C=N bond and a C-O-C bond. As a curing agent having a heterocycle, for example, a curing agent having an oxazoline group, a curing agent having an epoxy group, etc. can be cited. In addition, as a curing agent having a C=N bond, a curing agent having an oxazoline group, a curing agent having an isocyanate group, etc. can be cited. In addition, as a curing agent having a C-O-C bond, a curing agent having an oxazoline group, a curing agent having an epoxy group, polyurethane, etc. can be cited. The fact that the adhesive layer 5 contains a cured product of a resin composition of these curing agents can be confirmed by methods such as gas chromatography mass spectrometry (GCMS), infrared spectroscopy (IR), time-of-flight secondary ion mass spectrometry (TOF-SIMS), and X-ray photoelectron spectroscopy (XPS).
[0127] As the compound with isocyanate group, there is no particular restriction. From the viewpoint of effectively improving the adhesion of barrier layer 3 and adhesive layer 5, it is preferred to enumerate polyfunctional isocyanate compounds. Polyfunctional isocyanate compounds are not particularly limited as long as they are compounds with more than 2 isocyanate groups. As the specific example of polyfunctional isocyanate curing agent, pentane diisocyanate (PDI), isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HDI), toluene diisocyanate (TDI), diphenylmethane diisocyanate (MDI), compounds formed by polymerizing or ureate esterification, their mixtures or copolymers with other polymers, etc. can be enumerated. In addition, adducts, biuret bodies, isocyanurate bodies, etc. can be enumerated.
[0128] The content of the compound having an isocyanate group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0129] The compound with oxazoline radical is not particularly limited as long as it is the compound with oxazoline skeleton.As the object lesson of the compound with oxazoline radical, can enumerate the compound with polystyrene main chain, the compound with acrylic acid main chain etc.In addition, as commercially available product, for example can enumerate the EPOCROS series etc. of Japan Catalyst Co., Ltd. system.
[0130] The proportion of the compound having an oxazoline group in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0131] As a compound having an epoxy group, for example, an epoxy resin can be cited. As the epoxy resin, there is no particular limitation as long as it is a resin that forms a cross-linked structure by utilizing the epoxy group present in the molecule, and a known epoxy resin can be used. As the weight average molecular weight of the epoxy resin, preferably about 50 to 2000, more preferably about 100 to 1000, and even more preferably about 200 to 800. It should be noted that in the first invention, the weight average molecular weight of the epoxy resin is a value measured by gel permeation chromatography (GPC) under the condition of using polystyrene as a standard sample.
[0132] Specific examples of epoxy resins include glycidyl ether derivatives of trimethylolpropane, bisphenol A diglycidyl ether, modified bisphenol A diglycidyl ether, novolac glycidyl ether, glycerol polyglycidyl ether, polyglycerol polyglycidyl ether, etc. The epoxy resin may be used alone or in combination of two or more.
[0133] The proportion of the epoxy resin in the adhesive layer 5 is preferably in the range of 0.1 to 50 mass %, more preferably in the range of 0.5 to 40 mass %, in the resin composition constituting the adhesive layer 5. This can effectively improve the adhesion between the barrier layer 3 and the adhesive layer 5.
[0134] The polyurethane is not particularly limited, and known polyurethanes can be used. The adhesive layer 5 may be, for example, a cured product of a two-component curing type polyurethane.
[0135] The proportion of the polyurethane in the adhesive layer 5 is preferably in the range of 0.1 to 50% by mass, more preferably in the range of 0.5 to 40% by mass, in the resin composition constituting the adhesive layer 5. Thus, in an atmosphere where there are components that induce corrosion of the barrier layer such as an electrolyte, the adhesion between the barrier layer 3 and the adhesive layer 5 can be effectively improved.
[0136] It should be noted that when the adhesive layer 5 is a cured product of a resin composition comprising at least one selected from a compound having an isocyanate group, a compound having an oxazoline group and an epoxy resin and the above-mentioned acid-modified polyolefin, the acid-modified polyolefin functions as a main agent, and the compound having an isocyanate group, the compound having an oxazoline group and the compound having an epoxy group respectively function as a curing agent.
[0137] The thickness of the adhesive layer 5 is preferably about 50 μm or less, about 45 μm or less, about 30 μm or less, about 20 μm or less, or about 5 μm or less. In addition, the thickness of the adhesive layer 5 is preferably about 0.1 μm or more, about 0.5 μm or more, about 5 μm or more, about 10 μm or more, or about 15 μm or more. As the range of the thickness, preferably listed are about 0.1 to 50 μm, about 0.1 to 45 μm, about 0.1 to 30 μm, about 0.1 to 20 μm, about 0.1 to 5 μm, about 0.5 to 50 μm, about 0.5 to 45 μm, about 0.5 to 30 μm, about 0.5 to 20 μm, about 0.5 to 5 μm, about 5 to 50 μm, about 5 to 45 μm, about 5 to 30 μm, about 5 to 20 μm, about 10 to 50 μm, about 10 to 45 μm, about 10 to 30 μm, about 10 to 20 μm, about 15 to 50 μm, about 15 to 45 μm, about 15 to 30 μm, about 15 to 20 μm, etc.
[0138] More specifically, in particular, when the adhesive exemplified as the adhesive layer 2 or the cured product of the acid-modified polyolefin and the curing agent, preferably about 1 to 10 μm, more preferably about 1 to 5 μm. In addition, in particular, when the resin (acid-modified polyolefin, etc.) exemplified as the heat-fusible resin layer 4 is used, preferably about 5 to 50 μm, about 5 to 45 μm, about 10 to 50 μm, about 10 to 45 μm, about 15 to 50 μm, about 15 to 45 μm. It should be noted that, in the case where the adhesive layer 5 is the adhesive exemplified as the adhesive layer 2 or the cured product of the resin composition containing the acid-modified polyolefin and the curing agent, for example, the adhesive layer 5 can be formed by curing it by heating or the like after applying the resin composition. In addition, in the case of using the resin exemplified as the heat-fusible resin layer 4, for example, it can be appropriately formed by melt co-extrusion molding of the heat-fusible resin layer 4 and the adhesive layer 5.
[0139] [Surface coating layer 6]
[0140] For the purpose of improving at least one of the appearance design, electrolyte resistance, scratch resistance, and formability, the outer packaging material for a storage device of the present invention may have a surface covering layer 6 on the substrate layer 1 (on the side of the substrate layer 1 opposite to the barrier layer 3) as needed. The surface covering layer 6 is a layer located on the outermost side of the outer packaging material for a storage device when the storage device is assembled using the outer packaging material for a storage device.
[0141] The surface coating layer 6 can be formed of a resin such as polyvinylidene chloride, polyester, polyurethane, acrylic resin, or epoxy resin.
[0142] When the resin forming the surface coating layer 6 is a curable resin, the resin may be any type of a single-liquid curable resin or a two-liquid curable resin, preferably a two-liquid curable resin. Examples of the two-liquid curable resin include two-liquid curable polyurethane, two-liquid curable polyester, and two-liquid curable epoxy resin. Among these, two-liquid curable polyurethane is preferred.
[0143] As a two-liquid curable polyurethane, for example, a polyurethane containing a main agent containing a polyol compound and a curing agent containing an isocyanate compound can be cited. Preferably, a two-liquid curable polyurethane with a polyol such as a polyester polyol, a polyether polyol and an acrylic polyol as a main agent and an aromatic or aliphatic polyisocyanate as a curing agent is cited. In addition, as a polyol compound, a polyester polyol having a hydroxyl group in a side chain in addition to a hydroxyl group at the end of a repeating unit is preferably used. By forming the surface coating 6 with polyurethane, it is possible to impart excellent electrolyte resistance to the outer packaging material for a storage device.
[0144] In the surface coating layer 6, at least one of the surface and the interior of the surface coating layer 6 may contain additives such as the above-mentioned lubricant, anti-blocking agent, matting agent, flame retardant, antioxidant, tackifier, anti-static agent, etc. as required, depending on the functionality that the surface coating layer 6 or its surface should have. As additives, for example, microparticles with an average particle size of about 0.5nm to 5μm can be cited. The average particle size of the additive is the median particle size measured by a laser diffraction / scattering particle size distribution measuring device.
[0145] The additive may be any of inorganic and organic substances. In addition, there is no particular limitation on the shape of the additive, and examples thereof include spherical, fibrous, plate-like, amorphous, and flaky shapes.
[0146] As the specific example of additive, talc, silicon dioxide, graphite, kaolin, montmorillonite, mica, hydrotalcite, silica gel, zeolite, aluminum hydroxide, magnesium hydroxide, zinc oxide, magnesium oxide, aluminum oxide, neodymium oxide, antimony oxide, titanium oxide, cerium oxide, calcium sulfate, barium sulfate, calcium carbonate, calcium silicate, lithium carbonate, calcium benzoate, calcium oxalate, magnesium stearate, aluminum oxide, carbon black, carbon nanotube, high melting point nylon, acrylate resin, cross-linked acrylic acid, cross-linked styrene, cross-linked polyethylene, benzoguanamine, gold, aluminum, copper, nickel etc. can be listed. Additive can be used alone or in combination of two or more. Among these additives, from the viewpoints of dispersion stability and cost, preferably silicon dioxide, barium sulfate, titanium oxide are listed. In addition, various surface treatments such as insulation treatment, high dispersibility treatment etc. can also be implemented on the surface for additive.
[0147] The method of forming the surface coating layer 6 is not particularly limited, and an example thereof includes a method of applying a resin that forms the surface coating layer 6. When an additive is added to the surface coating layer 6, the resin mixed with the additive may be applied.
[0148] The thickness of the surface coating layer 6 is not particularly limited as long as the surface coating layer 6 can exert the above-mentioned function, and is, for example, about 0.5 to 10 μm, preferably about 1 to 5 μm.
[0149] 3. Method for manufacturing outer packaging material for power storage device
[0150] Regarding the method for manufacturing an outer packaging material for a storage device, there is no particular limitation as long as a laminated body having the layers of the outer packaging material for a storage device of the present invention can be obtained, and a method including the steps of laminating at least a base material layer 1, a barrier layer 3 and a heat-fusible resin layer 4 in order from the outside to the inside can be cited. Specifically, the method for manufacturing an outer packaging material for a storage device includes the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in order to obtain a laminated body, wherein the heat-fusible resin layer contains polypropylene and polyethylene, and an island structure is observed in a cross-sectional image obtained using a scanning electron microscope in a cross-sectional image of a cross section of the heat-fusible resin layer in a direction parallel to TD and in a thickness direction y, and in the cross-sectional image, relative to the total number of island portions of the island structure, the area of the island portions is 0.02 μm 2 The ratio of the total number of the following island portions is 80.0% or more.
[0151] As an example of a method for manufacturing an outer packaging material for a storage device of the present invention, the following is described. First, a laminated body (hereinafter sometimes referred to as "laminated body A") is formed in which a substrate layer 1, an adhesive layer 2, and a barrier layer 3 are laminated in sequence. The formation of the laminated body A can be performed by the following dry lamination method. Specifically, an adhesive for forming the adhesive layer 2 is applied on the substrate layer 1 or on the barrier layer 3 whose surface is chemically treated as required by a coating method such as a gravure coating method or a roller coating method. After drying, the barrier layer 3 or the substrate layer 1 is laminated, and the adhesive layer 2 is cured.
[0152] Next, a heat-fusible resin layer 4 is laminated on the barrier layer 3 of the laminate A. When the heat-fusible resin layer 4 is laminated directly on the barrier layer 3, the heat-fusible resin layer 45 can be laminated on the barrier layer 3 of the laminate A by a method such as a heat lamination method, an extrusion lamination method, or the like. In addition, when an adhesive layer 5 is provided between the barrier layer 3 and the heat-fusible resin layer 4, for example, the following methods can be cited: (1) a method of laminating the adhesive layer 5 and the heat-fusible resin layer 4 by extruding them on the barrier layer 3 of the laminate A (co-extrusion lamination method, tandem lamination method); (2) a method of separately forming a laminate having an adhesive layer 5 and a heat-fusible resin layer 4 laminated thereon and laminating it on the barrier layer 3 of the laminate A by a heat lamination method, or a method of forming a laminate having an adhesive layer 5 laminated on the barrier layer 3 of the laminate A and laminating it by a heat lamination method. (1) a method for laminating a heat-melting resin layer 4 on a heat-melting resin layer 4; (2) a method for laminating a heat-melting resin layer 4 on a heat-melting resin layer 4; (3) a method for laminating a heat-melting resin layer 4 on a heat-melting resin layer 4 pre-filmed in a sheet form by flowing a molten adhesive layer 5 between the barrier layer 3 of the laminate A and the heat-melting resin layer 4 pre-filmed in a sheet form through the adhesive layer 5 (sandwich lamination method); (4) a method for laminating a heat-melting resin layer 4 pre-filmed in a sheet form on the adhesive layer 5 by coating an adhesive for forming the adhesive layer 5 on the barrier layer 3 of the laminate A with a solution and then drying the adhesive layer 5, or a method for laminating the heat-melting resin layer 4 pre-filmed in a sheet form on the adhesive layer 5 by further baking the adhesive layer 5.
[0153] When the surface covering layer 6 is provided, the surface covering layer 6 is laminated on the surface of the substrate layer 1 on the opposite side to the barrier layer 3. The surface covering layer 6 can be formed, for example, by coating the above-mentioned resin for forming the surface covering layer 6 on the surface of the substrate layer 1. It should be noted that the order of the process of laminating the barrier layer 3 on the surface of the substrate layer 1 and the process of laminating the surface covering layer 6 on the surface of the substrate layer 1 is not particularly limited. For example, after the surface covering layer 6 is formed on the surface of the substrate layer 1, the barrier layer 3 can be formed on the surface of the substrate layer 1 on the opposite side to the surface covering layer 6.
[0154] As described above, a laminated body is formed which has, in sequence, a surface covering layer 6 arranged as required / a base material layer 1 / an adhesive layer 2 arranged as required / a barrier layer 3 / an adhesive layer 5 arranged as required / a hot-melt adhesive resin layer 4. In order to make the adhesion between the adhesive layer 2 and the adhesive layer 5 arranged as required stronger, the laminated body can be further subjected to a heat treatment.
[0155] In the outer packaging material for a storage device, each layer constituting the laminate can be subjected to a surface activation treatment such as corona treatment, sandblasting, oxidation treatment, ozone treatment, etc. as required to improve processing adaptability. For example, by subjecting the surface of the substrate layer 1 opposite to the barrier layer 3 to corona treatment, the printing adaptability of the surface of the substrate layer 1 to ink can be improved.
[0156] 4. Application of outer packaging materials for power storage devices
[0157] The outer packaging material for a storage device of the present invention is used in a packaging body for sealing and storing storage device elements such as a positive electrode, a negative electrode, an electrolyte, etc. That is, a storage device element including at least a positive electrode, a negative electrode, and an electrolyte can be stored in a packaging body formed by the outer packaging material for a storage device of the present invention to form a storage device.
[0158] Specifically, by using the outer packaging material for an electrical storage device of the present invention, an electrical storage device element including at least a positive electrode, a negative electrode, and an electrolyte is covered in a manner such that a flange portion (an area where the heat-fusible resin layers are in contact with each other) is formed at the periphery of the electrical storage device element so that the metal terminals connected to the positive electrode and the negative electrode protrude outward, and the heat-fusible resin layers of the flange portion are heat-sealed to each other, thereby providing an electrical storage device using the packaging material for an electrical storage device. It should be noted that when the electrical storage device element is accommodated in a packaging body formed by using the outer packaging material for an electrical storage device of the present invention, the packaging body is formed in a manner such that the heat-fusible resin portion of the outer packaging material for an electrical storage device of the present invention becomes the inner side (the surface in contact with the electrical storage device element).
[0159] The outer packaging material for the storage device of the present invention can be applied to storage devices such as batteries (including capacitors (condenser), capacitors (capacitor) and the like). In addition, the outer packaging material for the storage device of the present invention can be used for any type of primary battery and secondary battery, preferably a secondary battery. There is no particular restriction on the type of secondary battery to which the outer packaging material for the storage device of the present invention can be applied, for example, lithium ion batteries, lithium ion polymer batteries, all-solid batteries, lead batteries, nickel-hydrogen batteries, nickel-cadmium batteries, nickel-iron batteries, nickel-zinc batteries, silver oxide-zinc batteries, metal-air batteries, multivalent cation batteries, capacitors (condenser), capacitors (capacitor) and the like. Among these secondary batteries, lithium ion batteries and lithium ion polymer batteries can be cited as preferred applicable objects of the outer packaging material for the storage device of the present invention.
[0160] Example
[0161] Hereinafter, the present invention will be described in detail with reference to Examples and Comparative Examples, but the present invention is not limited to the Examples.
[0162] <Manufacturing of packaging materials for power storage devices>
[0163] Examples 1, 2 and Comparative Examples 1, 2
[0164] A polyethylene terephthalate (PET) film (thickness 12 μm) and a stretched nylon (ONy) film (thickness 15 μm) were prepared, and a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) (3 μm) was applied on the PET film and bonded to the ONy film as a substrate layer. In addition, an aluminum alloy foil (JIS H4160: 1994A8021H-O (thickness 40 μm)) was prepared as a barrier layer. Next, a two-component polyurethane adhesive (polyol compound and aromatic isocyanate compound) was applied on one surface of the aluminum alloy foil to form an adhesive layer (thickness 3 μm) on the barrier layer. Next, the adhesive layer on the barrier layer and the substrate layer (ONy film side) were laminated by dry lamination and then subjected to aging treatment, thereby producing a substrate layer / adhesive layer / barrier layer laminate. Chemical surface treatment was applied to both surfaces of the aluminum alloy foil. The chemical surface treatment of the aluminum alloy foil is carried out as follows: a treatment solution containing a phenolic resin, a chromium fluoride compound and phosphoric acid is applied to the foil in such a manner that the coating amount of chromium is 10 mg / m 2 The precipitate was applied to both surfaces of an aluminum alloy foil by a roll coating method and then baked.
[0165] Then, maleic anhydride-modified polypropylene as an adhesive layer (thickness 40 μm) and random polypropylene (a composition of random polypropylene and polyethylene) as a heat-fusible resin layer (thickness 40 μm) were melt-coextruded on the barrier layer of each laminate obtained above, and the heat-fusible resin layer side was brought into contact with a cooling roller for cooling (cooling conditions A or B described later, respectively), thereby laminating an adhesive layer / heat-fusible resin layer on the barrier layer to obtain an outer packaging material for a storage battery device (total thickness 153 μm) in which a base layer (thickness 30 μm including an adhesive) / adhesive layer (3 μm) / barrier layer (40 μm) / adhesive layer (40 μm) / heat-fusible resin layer (40 μm) were laminated in sequence. In Example 2, the content of polyethylene contained in the heat-fusible resin layer was reduced compared with Example 1. In Comparative Example 1, the content of polyethylene contained in the heat-fusible resin layer was increased compared with Example 1. In Comparative Example 2, the composition of the heat-adhesive resin layer was set to be the same as that of Example 1, and cooling condition B was adopted.
[0166] (cooling conditions)
[0167] The conditions for cooling the heat-adhesive resin layer side by contacting the cooling roll are as follows. Table 1 shows the cooling conditions used in Examples and Comparative Examples.
[0168] Cooling condition A: The difference between the temperature of the melt coextruded molten resin (molten resin forming the thermally fusible resin layer) and the surface temperature of the cooling roller is set to 70°C or more, which is set to the condition for rapidly cooling the molten resin to form the thermally fusible resin layer (the condition for inhibiting the crystal growth of polyethylene).
[0169] Cooling condition B: The difference between the temperature of the melt coextruded molten resin (molten resin forming the thermally adhesive resin layer) and the surface temperature of the cooling roll is set to 50° C. or less, and the molten resin is gradually cooled to form the thermally adhesive resin layer.
[0170] <Measurement of the ratio between the area and number of islands in a sea-island structure>
[0171] The outer packaging material for the storage device is embedded in a thermosetting epoxy resin and cured. A commercially available rotary ultrathin slicer (EMUC6 manufactured by LEICA) and a glass knife are used to make a section parallel to the TD and in the thickness direction. At this time, the section is made using room temperature ultrathin sections. The heat-fusible resin layer of the outer packaging material for the storage device together with the embedding resin is stained with ruthenium tetroxide for 3 hours. After staining, the resin swells and the island structure cannot be confirmed near the section, so the swollen part is trimmed using an ultrathin slicer. After that, a diamond knife is used to sample the section after cutting off about 1μm to 2μm, and the stained section with a thickness of about 100nm is observed in the following manner. For the stained section, a field emission scanning electron microscope (S-4800 manufactured by Hitachi High-Tech Co., Ltd.) is used to obtain a cross-sectional image. It should be noted that the cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the opposite side of the barrier layer to the portion of 12.5% thickness, with the total thickness of the layer located inside the barrier layer being 100%. The measurement conditions are: acceleration voltage: 30 kV, emission current: 10 μA, detector: transmission detector, tilt: none (0°), and observation magnification 5000 times. Afterwards, the cross-sectional image is binarized using image processing software (image analysis software attached to Keyence electron microscope VHX-5000) that can perform binarization. Specifically, the measurement can be started with the brightness (standard) condition of the image analysis software, the extraction area (measurement range) is set to a rectangular shape (7 μm in length and 13 μm in width), the shooting size is set to standard (1600×1200), the tilt angle is set to 0 degrees, the shooting mode is set to normal shooting, and the extraction object is "dark area". In addition, the unextracted parts and the redundant extractions are corrected by automatic measurement, and the total area and total number of the extracted positions (islands) are measured. At this time, the area and number of all islands existing in the extraction area are measured. Using the acquired data, the ratio of the total area of all islands to the area of the measurement range of the cross-sectional image (total area of islands / area of the measurement range of the cross-sectional image) is calculated. The area of all islands is 0.01 μm 2 The ratio of the total number of islands below (0.01 μm 2 The total number of islands below / the total number of all islands), 0.02 μm 2 The ratio of the total number of islands below (0.02 μm 2 The total number of islands below / the total number of all islands), 0.03 μm 2 The ratio of the total number of islands below (0.03 μm 2 The total number of islands below / the total number of all islands), 0.30 μm 2The ratio of the total number of islands above 0.30 μm 2 The total number of islands above / the total number of all islands), 0.15 μm 2 The ratio of the total number of islands above 0.15 μm 2 The results are shown in Table 1.
[0172] <Whitening due to molding>
[0173] Each power storage device packaging material was cut into a rectangular shape of 90 mm in length (MD) and 150 mm in width (TD) as a test sample. The MD of the power storage device packaging material corresponds to the rolling direction (RD) of the aluminum alloy foil, and the TD of the power storage device packaging material corresponds to the TD of the aluminum alloy foil. The test sample was subjected to an environment of 25°C using a rectangular molding die (female mold, the maximum height roughness (nominal value of Rz) of the surface specified in Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002 is 3.2 μm. Corner R2.0 mm, ridge R1.0 mm) having a diameter of 31.6 mm (MD) × 54.5 mm (TD) and a corresponding molding die (male mold, the maximum height roughness (nominal value of Rz) of the surface of the ridge portion is 1.6 μm according to Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002, and the maximum height roughness (nominal value of Rz) of the surface other than the ridge portion is 1.6 μm according to Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002. 0659-1:2002 Appendix 1 (reference) The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet is 3.2μm. Corner R2.0mm, ridgeline R1.0mm), cold forming (deep drawing 1 stage forming) is performed at a pressing pressure (surface pressure) of 0.1MPa in such a way that the forming depth reaches 6.0mm. At this time, the above test sample is placed on the female mold for forming in such a way that the heat-fusible resin layer side is located on the male mold side. In addition, the gap between the male mold and the female mold is 0.3mm. Visually observe the heat-fusible resin layer of the test sample after forming to confirm whether it is whitened. The sample without whitening is evaluated as A, the sample with only a little whitening is evaluated as B, and the sample with obvious whitening is evaluated as C. The results are shown in Table 1. Among them, the whitened part is mainly around the side wall on the short side of the forming part.
[0174] <Insulation>
[0175] The outer packaging material for the storage device is cut into a sheet with a length (MD) of 160 mm and a width (TD) of 90 mm. The sheet is formed at 25°C using a rectangular molding die (female mold, the maximum height roughness (nominal value of Rz) of the surface is 3.2 μm as specified in Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002. Corner R2.0 mm, ridge R1.0 mm) and a corresponding molding die (male mold, the maximum height roughness (nominal value of Rz) of the surface of the ridge part is 1.6 μm as specified in Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002, and the surface other than the ridge part is 1.6 μm as specified in Table 2 of the surface roughness standard sheet for comparison in Appendix 1 (reference) of JIS B 0659-1:2002. 0659-1:2002 Appendix 1 (reference) The maximum height roughness (nominal value of Rz) specified in Table 2 of the comparative surface roughness standard sheet is 3.2μm. Corner R2.0mm, ridgeline R1.0mm), cold forming (deep drawing 1 stage forming) is performed at a pressing pressure (surface pressure) of 0.1MPa in such a way that the forming depth reaches 3.0mm. Next, the formed sample sheet is folded in half in the MD direction so that the heat-fusible resin layers are opposite to each other, and cut so that the width from the forming part to the end on the MD side becomes 3mm to obtain a formed body. Regarding the position of the forming part, the intervals between the forming part and the two end edges of the sheet piece in TD are 25mm and 32mm respectively.
[0176] Next, prepare a polyethylene terephthalate plate (PET plate) with a thickness of 3.0 mm, a length (MD) of 30.0 mm, and a width (TD) of 52.5 mm and an aluminum terminal with a thickness of 70 μm, a length (MD) of 55 mm, and a width (TD) of 5 mm. A tab film (formed by maleic anhydride-modified polypropylene) with a thickness of 100 μm and a width of 10 mm is wound on the central part of the aluminum terminal. Using paper tape, the aluminum terminal is attached to the end of the MD of the PET plate, and the PET plate is inserted into the molding part of the above-mentioned molded body. At this time, the aluminum terminal protrudes from the molding part to the outside of the molded body, and the tab film is located between the heat-fusible resin layers of the molded body. In this state, the end edge of the molded body protruding with the aluminum terminal is heat-fused under the conditions of a width of 3 mm, a surface pressure of 4.0 MPa, a sealing temperature of 170°C, and a sealing time of 3.0 seconds. Next, one end perpendicular to the heat-fused end was heat-fused under the conditions of 3 mm width, 1.0 MPa surface pressure, 170°C sealing temperature, and 3.0 seconds sealing time to form the molded body into a bag. Next, the bag-shaped molded body was stored in a dry room for 1 day, and an electrolyte (an electrolyte obtained by mixing lithium hexafluorophosphate in a solution mixed at a volume ratio of ethylene carbonate: diethyl carbonate: dimethyl carbonate = 1:1:1) was poured from the remaining end (opening) of the opening, and the opening was heat-fused under the conditions of 3 mm width, 1.0 MPa surface pressure, 170°C sealing temperature, and 3.0 seconds sealing time to seal the electrolyte in the molded body. Finally, the molded body was stored at 60°C for 6 hours with the heat-fused end facing up. Next, between the last heat-fused end and the molded portion, along the molded portion, the heat-fusible resin layers were heat-fused to each other at a width of 3 mm, a surface pressure of 1.0 MPa, a sealing temperature of 170°C, and a sealing time of 3.0 seconds to produce a test sample in which the electrolyte was sealed in the molded portion.
[0177] Next, for the obtained test samples, the insulation between the barrier layer and the aluminum terminal of the test samples was evaluated using a tester (Insulation Resistance Tester 3154 manufactured by Hioki Electric). First, 10 test samples were prepared separately. After that, one terminal of the tester was connected to the aluminum terminal of the test sample, and the other terminal was connected to the barrier layer of the outer packaging material of the storage device, respectively, using alligator clips for connection. Next, a voltage of 25V was applied between the testers, and samples with a resistance value of more than 200MΩ after 10 seconds were marked as qualified (OK), and samples with a resistance value of less than 200MΩ after 10 seconds were marked as unqualified (NG). The number of unqualified (NG) test samples among the 10 test samples is shown in Table 1.
[0178] [Table 1]
[0179]
[0180] In Table 1, "PE" means polyethylene.
[0181] As can be seen from the description in Table 1, in the cross-sectional image of the heat-fusible resin layer containing polypropylene and polyethylene, in the outer packaging materials for power storage devices of Examples 1 and 2, the area of the island portions is 0.02 μm with respect to the total number of island portions of the sea-island structure. 2 The total number of the following island portions is 80.0% or more, and whitening and a decrease in insulation properties due to molding are effectively suppressed.
[0182] As described above, the present invention provides the following aspects of the invention.
[0183] Item 1. An outer packaging material for a power storage device, which is composed of a laminate having at least a base layer, a barrier layer and a heat-fusible resin layer in this order from the outside to the inside,
[0184] The heat-fusible resin layer comprises polypropylene and polyethylene.
[0185] The sea-island structure can be observed in a cross-sectional image of the heat-fusible resin layer taken in a direction parallel to TD and in the thickness direction using a scanning electron microscope.
[0186] The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%.
[0187] In the cross-sectional image, the area of the islands is 0.02 μm with respect to the total number of islands in the sea-island structure. 2 The ratio of the total number of the following island portions is 80.0% or more.
[0188] Item 2. The outer packaging material for a power storage device according to Item 1, wherein
[0189] In the cross-sectional image of the thermally adhesive resin layer, a ratio of a total area of the island portions of the sea-island structure to an area of a measurement range of the cross-sectional image is 12.0% or less.
[0190] Item 3. The outer packaging material for a power storage device according to Item 1 or 2, wherein
[0191] In the cross-sectional image of the thermally fusible resin layer, the area of the island portions is 0.03 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the following island portions is 90.0% or more.
[0192] Item 4. The outer packaging material for a power storage device according to any one of Items 1 to 3, wherein
[0193] In the cross-sectional image of the thermally fusible resin layer, the area of the island portions is 0.01 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the following island portions is 50.0% or more.
[0194] Item 5. The outer packaging material for a power storage device according to any one of Items 1 to 4, wherein
[0195] In the cross-sectional image of the thermally fusible resin layer, the area of the island portions is 0.30 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the above island portions is 1.0% or less.
[0196] Item 6. The outer packaging material for a power storage device according to any one of Items 1 to 5, wherein
[0197] An adhesive layer is provided between the barrier layer and the heat-adhesive resin layer.
[0198] Item 7. The outer packaging material for a power storage device according to Item 6, wherein
[0199] The adhesive layer has a thickness of 5 μm or more.
[0200] Item 8. A method for producing an outer packaging material for a power storage device, wherein:
[0201] The method comprises the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in order from the outside to the inside to obtain a laminated body,
[0202] The heat-fusible resin layer comprises polypropylene and polyethylene.
[0203] The sea-island structure can be observed in a cross-sectional image of the heat-fusible resin layer taken in a direction parallel to TD and in the thickness direction using a scanning electron microscope.
[0204] The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%.
[0205] In the cross-sectional image, the area of the islands is 0.02 μm with respect to the total number of islands in the sea-island structure. 2 The ratio of the total number of the following island portions is 80.0% or more.
[0206] Item 9. A power storage device, wherein:
[0207] An electric storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a packaging body formed of the outer packaging material for an electric storage device according to any one of items 1 to 7.
[0208] Explanation of symbols
[0209] 1. Base material layer
[0210] 2 Adhesive layer
[0211] 3 Barrier layer
[0212] 4Thermal fusible resin layer
[0213] 5. Adhesive layer
[0214] 6 Surface covering
[0215] 10 Outer packaging materials for power storage devices.
Claims
1. An outer packaging material for an electric storage device, characterized in that: The invention is composed of a laminated body having at least a base material layer, a barrier layer and a heat-fusible resin layer in this order from the outside to the inside, The heat-fusible resin layer includes polypropylene and polyethylene, A sea-island structure can be observed in a cross-sectional image of the heat-adhesive resin layer taken in a direction parallel to TD and in the thickness direction using a scanning electron microscope. The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%. In the cross-sectional image, the area of the island portion is 0.02 μm relative to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the following island portions is 80.0% or more.
2. The outer packaging material for an electric storage device according to claim 1, wherein: In the cross-sectional image of the thermally adhesive resin layer, a ratio of a total area of the island portions of the sea-island structure to an area of a measurement range of the cross-sectional image is 12.0% or less.
3. The outer packaging material for an electrical storage device according to claim 1 or 2, wherein: In the cross-sectional image of the thermally fusible resin layer, the area of the island portions relative to the total number of island portions of the sea-island structure is 0.03 μm 2 The ratio of the total number of the following island portions is 90.0% or more.
4. The outer packaging material for an electrical storage device according to any one of claims 1 to 3, wherein: In the cross-sectional image of the thermally adhesive resin layer, the area of the island portions is 0.01 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the following island portions is 50.0% or more.
5. The outer packaging material for an electrical storage device according to any one of claims 1 to 4, wherein: In the cross-sectional image of the thermally fusible resin layer, the area of the island portions is 0.30 μm with respect to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the above island portions is 1.0% or less.
6. The outer packaging material for an electrical storage device according to any one of claims 1 to 5, wherein: An adhesive layer is provided between the barrier layer and the thermally adhesive resin layer.
7. The outer packaging material for an electric storage device according to claim 6, wherein: The thickness of the adhesive layer is greater than 5 μm.
8. A method for manufacturing an outer packaging material for an electrical storage device, characterized in that: The method comprises the steps of laminating at least a base material layer, a barrier layer and a heat-fusible resin layer in order from the outside to the inside to obtain a laminated body, The heat-fusible resin layer includes polypropylene and polyethylene, A sea-island structure can be observed in a cross-sectional image of the heat-adhesive resin layer taken in a direction parallel to TD and in the thickness direction using a scanning electron microscope. The cross-sectional image is a cross-sectional image obtained from the surface of the heat-fusible resin layer on the side opposite to the barrier layer to a portion having a thickness of 12.5%, with the total thickness of the layers located on the inner side of the barrier layer being 100%. In the cross-sectional image, the area of the island portion is 0.02 μm relative to the total number of island portions of the sea-island structure. 2 The ratio of the total number of the following island portions is 80.0% or more.
9. An electric storage device, characterized in that: An electric storage device element including at least a positive electrode, a negative electrode, and an electrolyte is housed in a packaging body formed of the outer packaging material for an electric storage device according to any one of claims 1 to 7.
